Performance Of Poly(Vinyl Alcohol) Asymmetric Membrane Incorporated With Graphene Oxide For Pervaporation Dehydration Of Ethanol Aqueous Solution - Kamal, Muhammad Zuber Al Awwam Mustapa (Universiti Sains Malaysia, 2017)
Using phase inversion and solution casting method, polyvinyl alcohol/polyvinylidene fluoride (PVA/PVDF) incorporated with graphene oxide (GO) membrane was prepared and compared with pure PVA/PVDF membranes. The resultant membranes were characterized by using scanning electron microscopy (SEM), mechanical tensile test, and degree of swelling. The resultant membranes performance were studied on the pervaporation of dehydration of 95wt% ethanol aqueous solution. The results showed that the incorporation of GO sheets onto the PVA/PVDF membrane increased the total permeate flux with 296.6 g/m2.h as compared to 257.5 g/m2.h achieved by pure PVA/PVDF membrane. Further characterization on the permeate samples showed that the permeate through GOPVA/ PVDF membrane exhibited higher separation factor of 557.6, approximate doubled the value obtained by pure PVA/PVDF membrane with 249.5 only. Thus, this lead to higher pervaporation separation index obtained by GO-PVA/PVDF membrane as compared pure PVA/PVDF membrane with 159,925 g/m2.h and 59,690 g/m2.h respectively. In conclusion, the incorporation of GO sheets onto the membrane capable to overcome the trade-off between the total permeation flux and separation factor, thus enhance the overall performance of the pervaporation process.